Towards a renewed philosophy of nature in the West: making sense of our place in the world in conversation with Pierre Hadot - Fourie-Basson, Wiida Elizabeth (Stellenbosch : Stellenbosch University, 2023)
Thesis (MPhil)--Stellenbosch University, 2023.